Anti-Inflammatory Activity of White Radish Tuber Ethanol Extract (Raphanus sativus L.) Induced by Carrageenan - Evi Kurnia Ningsih; Wahyu Yuliana Solikah; Rizal Fauzi; Daru Estiningsih (LPPM Akafarma Sunan Giri Ponorogo, 2026)
Indonesia possesses abundant natural resources with significant potential for the development of nutraceutical foods and traditional medicines. However, many local plants remain insufficiently studied regarding their efficacy and safety. One promising plant is the white radish tuber (Raphanus sativus L.), which offers various health benefits and potential as a functional food ingredient. This study aims to evaluate the anti-inflammatory effect of the ethanol extract of white radish tubers on paw edema in male Wistar rats (Rattus norvegicus) induced with 1% carrageenan. The research employed a laboratory experimental design, producing ethanol extracts using three solvent concentrations—50%, 70%, and 96%—followed by phytochemical screening. Anti-inflammatory activity was tested using five treatment groups: a negative control (1% CMC-Na), a positive control (diclofenac sodium 2.25 mg/kgBW), and three extract groups administered at 300 mg/kgBW according to the respective ethanol concentrations. The primary parameter measured was the volume of edema formed in the rats’ paws. Phytochemical screening revealed that the ethanol extract contained secondary metabolites such as alkaloids, flavonoids, saponins, and tannins, all known to possess anti-inflammatory properties. The extracts produced edema inhibition rates of 31.02% (50%), 21.80% (70%), and 18.44% (96%), comparable to diclofenac sodium at 18.63%. Statistical analysis using one-way ANOVA indicated an overall difference among the treatment groups. However, post-hoc Tamhane T2 analysis demonstrated that the anti-inflammatory activities of the 50%, 70%, and 96% ethanol extracts were not significantly different (p > 0.05), although all extract groups exhibited anti-inflammatory activity comparable to diclofenac sodium.